Children's Reasoning about Poverty, Economic Mobility, and Helping Behavior: Results of a Curriculum Intervention in the Early School Years. (December 2016) - Mistry, Rashmita S.; Nenadal, Lindsey; Griffin, Katherine M.; Zimmerman, Frederick J.; Cochran, Hasmik Avetisian; Thomas, Carla‐Anne; Wilson, Christopher
Abstract : This study evaluated the efficacy of an inquiry‐based poverty curriculum unit on students' beliefs about causes of poverty, economic mobility, and helping behaviors. Participants were 89 kindergarten, first‐ and second‐grade students (mean age = 6.81 years, SD = .93) across two intervention and two control classrooms. Students in intervention classrooms participated in a 5‐ to 7‐week curriculum unit focused on poverty. Preintervention results showed no differences in outcomes by condition. Postintervention results indicated that, compared to the control condition, students in the intervention were more likely to say that poverty is malleable over time and less likely to suggest giving money to poor families as a way to help. There were no differences, however, by condition in the types of causal attributions that students provided (i.e., individualistic, fatalistic, and structural). Implications for theory and educational practice regarding teaching about economic inequality and mobility are discussed.